Clinicopathological changes in guinea pigs (Cavia porcellus linnaeus) following infection by Leptospira icterohaemorrhagiae serovar Lai Strain Langkawi - Tyagita, . (2012)
Leptospirosis is a zoonosis of worldwide distribution caused by infection with pathogenic spirochetes of the genus Leptospira. Interaction between human and mammalian reservoir is the main factor of the transmission of the disease, where human can be infected through direct contact with the infected animals or through exposure to fresh water or soil contaminated by infected animal urine. Unfortunately, the number of cases of leptospirosis in humans is apparently under reported. Information on leptospiral infection in domestic animals is still lacking and this could impede the understanding of the epidemiology and pathogenesis of the disease which later allows the implementation of control programs of leptospiral infection in Malaysia. This study was expected to learn the clinical symptoms and pathological changes in guinea pigs infected with Leptospira icterohaemorrhagiae serovar Lai strain Langkawi; and provide a better understanding of the pathogenesis of leptospirosis. Three-week old of 17 guinea pigs (Cavia porcellus linnaeus) of approximately 250-300 grams body weight were used in this study. There were five treated groups (n=3), injected with 106 of low-passage L. icterohemorrhagiae serovar Lai strain Langkawi and two guinea pigs were injected with EMJH liquid intraperitoneally as negative control. The animals were observed and recorded daily for clinical signs (started from the animal arrived to the animal house and during the experiments processed), which include presence of discharge, respiratory distress, body temperature, mucous membrane and icterus. The animals were sacrificed serially beginning from Day 1 until day 7 p.i. The negative control guinea pigs were sacrificed on Day 0 and Day 7 p.i. Blood samples were taken for MAT pre (Day 0) and post infections (Days 1, 2, 3, 5 and 7 p.i) from both groups, while the lung, liver, kidney and spleen were removed from 3 sacrificed guinea pigs per each serial killing day (on Days 1, 2, 3, 5 and 7 p.i) for light microscopy (H&E stain and silver stain), ultrastructural (transmission electron microscopy) and molecular studies (polymerase chain reaction). Alteration of body temperature, dehydrated, droopy eyes and jaundice, were noted since day 1 until day 7 p.i. Sudden death was found in guinea pig on day 5 and day 7 p.i. Hematology and biochemistry test result were observed low level of total white blood cells (WBC), neutrophils and lymphocyte significantly on day 7 p.i. The decline of thrombocytes, red blood cells (RBC) and hemoglobin (Hb) were also noted, however it was not significant. There were enhancement level of electrolytes such as sodium (Na),Chlore (Cl), and potassium (K) insignificantly. The data also mentioned that the level of aspartate aminotransferase (AST), both total bilirubin and conjugated bilirubin were increased. For albumin, alanine transaminase (ALT), blood urea nitrogen (BUN), total protein and creatinine showed the opposite result. While significant changes was can be seen in the low alkaline phosphatase (ALP) gradually. Histopathological changes such as congestion, hemorrhages and edema were overlooked in all represent organs (lung, liver, kidney and spleen) started since day 1 p.i, contained inflammatory cells infiltration (neutrophil, lymphocytes and macrophages), degenerated and necrotic cells, vascular wall injuries and hemolysis. The chronic active hepatitis which occurred on day 5 p.i, had altered blood circulation through fibrosis. Thrombi were found in the liver and glomerular capillaries. Hydropic degeneration indicating progressive ischemia in the livers and kidneys were observed on day 5 up to day 7 p.i. On silver staining, leptospires were found adjacent to the central veins and in bile canaliculi at sites of centrilobular necrosis in the liver. In the kidneys, leptospires were detected in the interstitium adjacent to renal corpuscles, proximal and distal tubules and also collecting tubules of the kidneys. Leptospires were also detected in the red and white pulp of the spleen, sinusoid of the red pulps, lymphocytes and vascular wall both in red and white pulp. Transmission electron microscopy (TEM) examination of the lungs showed that Leptospira was only observed outside the alveolar capillary on Day 3 p.i. Necrotic white pulps were evidenced by cellular degeneration on Day 7 p.i as a result under the electron microscope, no intracellular Leptospira was seen in the hepatocytes. However, Leptospira were observed adjacent and appeared attached to the hepatocyte cell membrane on Day 3 p.i and the Leptospira captured in sinusoid causing ruptured membrane of the hepatocytes on Day 5 p.i. In the kidneys, Leptospira was adjacent to degenerated tubular cells at the interstitial junction. Serum samples from the guinea pigs (negative control and the treated groups) were subjected to the microscopic agglutination test (MAT). Antibody against the Leptospira could be seen in serum samples of the guinea pigs sacrificed on Day 5 p.i (2 guinea pigs) and on Day 7 p.i (2 guinea pigs). The lowest seropositivity was 1:40 for guinea pigs sacrificed on Day 5 p.i, while the highest one was 1:320 for guinea pigs that were sacrificed on Day 7 p.i. The PCR findings revealed Leptospira were in the liver on Day 3 p.i and in the kidney on day 7 p.i. All findings were suggestive of leptospirosis which fulfills the objectives of this study.